2021
DOI: 10.3390/mi12070768
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Synthesis, Control, and Sensing of Magnetic Nanoparticles: A Review

Abstract: Magnetic nanoparticles have attracted significant attention in various disciplines, including engineering and medicine. Microfluidic chips and lab-on-a-chip devices, with precise control over small volumes of fluids and tiny particles, are appropriate tools for the synthesis, manipulation, and evaluation of nanoparticles. Moreover, the controllability and automation offered by the microfluidic chips in combination with the unique capabilities of the magnetic nanoparticles and their ability to be remotely contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 171 publications
(181 reference statements)
0
42
0
Order By: Relevance
“…Moreover, droplet coalescence has to be avoided to provide the same reaction conditions in each droplet, and to ensure a reliable processing [75]. The generation of droplets in segmented flow can be achieved by several techniques, which include T-junction, flow focusing and co-flow [76,77]. As shown in Figure 3C, the droplet is formed in a T-junction by shear forces and liquid-liquid interfacial tension at the surface of the capillary.…”
Section: Microfluidic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, droplet coalescence has to be avoided to provide the same reaction conditions in each droplet, and to ensure a reliable processing [75]. The generation of droplets in segmented flow can be achieved by several techniques, which include T-junction, flow focusing and co-flow [76,77]. As shown in Figure 3C, the droplet is formed in a T-junction by shear forces and liquid-liquid interfacial tension at the surface of the capillary.…”
Section: Microfluidic Synthesismentioning
confidence: 99%
“…Coating (for example by poly-l-lysine) to obtain stable nonpyrogenic MNP suspension [115] product homogeneity quality reduction by concentration gradients and hot spots in the reaction flask [25,51] enhanced quality due to homogeneous morphology, narrow size distribution [25,67,116] high within one bacteria strain but strain variation possible [52][53][54]95] reproducibility, production rate and scale-up capability significant batch to batch variations in size, morphology, and magnetic properties [25,111,[117][118][119], poor scaling up capability. A reported study from Lin et al showed a production rate of 4.73 g/h for microfluidic synthesis comparing to 1.4 g/h for conventional synthesis with the same conditions [89] continuous production, no batch-to-batch variation, high scale-up capability high at the defined environmental conditions [92], mg/(L • day) production rate [52], high scale-up capability, though challenging due to long term bacteriostatic growth conditions [38,40,46,78] clogging not applicable microchannel-wall blocking during nucleation or by agglomeration [77,104,[120][121][122] not applicable automation poor feasible/integratable [66,123,124] capability of online characterization not applicable for batch, though magnetic characterization of whole batches by magnetic particle spectroscopy is feasible parameter control and synthesis adjustment feasible during synthesis, control of magnetic parameters by magnetic particle spectroscopy [25,125] and NMR [126] cost low, common lab equipment expensive microreactor fabrication expensive specialized equipment…”
Section: Comparison Of Different Synthesesmentioning
confidence: 99%
“…Moreover, this microfluidic-based magnetometer can be integrated into microfluidic chips, which have been recently used for magnetic particle synthesis, 30–32 for online magnetic susceptibility characterization. 33 Since this technology allows estimation of the particle magnetic susceptibility at the single-particle level, it provides control feedback signals soon after the synthesis of the first particles to adjust the production parameters. Thus, it lowers the waste particles and the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors 2021, 21, x FOR PEER REVIEW 2 of 14 well suited for automation, and improve assay sensitivity, magnetic beads-based assays are commonly used in various bioassays and for biosensing applications [15][16][17][18][19]. Previously, we introduced a novel platform that uses magnetically modulated biosensors (MMB) to rapidly detect very low concentrations of antibodies [20], proteins [21], and specific nucleic acid sequences [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Other inhibitor screening assays that rely on magnetic beads (e.g., flow cytometry) are also used for the high throughput screening of inhibitors [ 14 ]. Because magnetic beads facilitate the separation steps, are well suited for automation, and improve assay sensitivity, magnetic beads-based assays are commonly used in various bioassays and for biosensing applications [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%